Optimasi desain rencana tanggul lepas pantai NCICD di Teluk Jakarta terhadap kemungkinan tsunami akibat letusan Gunung Anak Krakatau - Huda Bachtiar; Riam Badriana; Leo Sembiring; Didit Adytia; I Putu Samskerta; Andonowati Andonowati; E. van Groesen (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2017)
The infrastructural plans in the Jakarta Bay to reduce risks of flooding in Jakarta city comprise a large sea dike that encloses a retention lake. Part of the planned dike has the shape of the iconic Garuda bird. This shape is based on NCICD Stage-B Master Plan, where the form shape has not been tested on hydraulic perspective. Therefore, testing of wave run-up has been investiagated to find the optimum form of the Garuda Shape. The simulation of wave run-up uses Hawassi Model, where the model is governed by Boussinesq wave equation with considering wave-wave interaction. This paper shows that if in the future an explosion of Anak Krakatau will occur with strength 1/4th of the original Karkatau 1883 explosion, wave crests of 11m and troughs of 6m may collide against the birds head. As an alternative example, a more optimized design of the dike is constructed that reduces the maximal wave effects considerably.